OPTIMALISASI PROGRAM ASUHAN MANDIRI TANAMAN OBAT KELUARGA (ASMANTOGA) UNTUK MENINGKATKAN KUALITAS KESEHATAN DAN PEREKONOMIAN MASYARAKAT DUSUN TEGALREJO DESA AMPELGADING - Isna Nurul Inayati; Rofiqoh Firdausi; Nanik Ulfa (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
KKN thematic conducted by Islamic University Raden Rahmat is an important part of the initiative Khaira Ummah, an important agenda of Islamic University Raden Rahmat that has the mind to create the village Khaira Ummah. One of the target villages, namely Tegalrejo village, Ampelgading villages in Selorejo District, Blitar, is known that the initial condition of Tegalrejo Hamlet has abundant family medicinal plants, but has not been managed and well utilized. In regard to the condition, the optimization of the self-care program of the Family Medicine plant (Asmantoga) is carried out with the aim of health quality and the community economy of Tegalrejo village increases. There are two approaches that authors use in the optimization of Asmantoga program, namely Apreciative Inquiry and Working Out Loud. Both approaches are then outlined in the five stages of implementation of the program, namely Phase 1 (15-23 February 2019): Planning Program, Phase 2 (24 February – 13 March 2019): Pioneering Asmantoga Educational Park, Phase 3 (3-7 March 2019): Planning and Making Asmantoga Cookbook, Stage 4 (8-9 Maret2019): implementation of Workshop and socialization, Phase 5 (15 March 2019): Inauguration and Asmantoga Educational Park handover. From 5 stages of implementation of activities that have been applied, it can be concluded that the optimization of Asmantoga program is stated to improve the health and economic quality of the village Tegalrejo district of Ampelgading subdistrict Malang district.